PECULIARITIES IN THE DEVELOPMENT OF SPECIAL ECONOMIC ZONES AND INDUSTRIAL PARKS IN RUSSIA - Sergey SOSNOVSKIKH (European Journal of Geography)
This paper investigates the process of developing and implementing Special Economic Zones (SEZs) and industrial parks in Russia. Governments commonly use SEZ policies to develop and diversify exports, create jobs, and launch technology and knowledge sharing. The industrial cluster concept is based on the significance of rivalry and supplier networks within the cluster, the combination of geographical specificities and government policies that lead to innovation and productivity growth. This study reveals that, in Russia, the government’s approach in developing these initiatives has strongly interfered with business activities and prevented the vital competitive and collaborative behavior of firms within these economic zones.